The Purchase Decision to ABC Sauce in Kebumen Regency - Winda Istianti; Heru Irianto; Erlyna Wida Riptanti (Jurnal Social Economic of Agriculture, 2023)
This analysis on purchasing decisions for ABC sauce in Kebumen Regency has the aim of knowing the effect of brand image, characteristic products, and cost on purchasing decisions for ABC sauces. This study was conducted on consumers who consume ABC brand sauce products, are domiciled in Kebumen Regency, and have a minimum age of 20 years. The respondent of this study is 100 people and was collected by using purposive sampling. Data were obtained through in-depth interviews and observation in the existing sub-districts. The analytical method used is SEM-PLS. The output of this analysis regarding the purchase decision of ABC sauce illustrates that the purchase decision of ABC sauce is not influenced by the brand image variable, but the purchase decision of ABC sauce in Kebumen Regency is influenced by the product quality and product price. ABC sauce producers must pay attention to the factors that influence consumer purchasing decisions such as product quality and price. Indicators of product quality are the suitability of benefits with needs, a guarantee of safety, product features, and quality. Indicators of price are affordable prices, prices according to product quality, chili prices can compete with similar products, and according to the needs and abilities of consumers.